Evaluation of Simplified Analysis Procedures for a High-Rise Reinforced Concrete Core Wall Structure - Abdur Rahman; Qaiser Uz Zaman Khan; Muhammad Irshad Qureshi (Advances in Civil Engineering)
Nonlinear response history analysis (NLRHA) procedure is one of the most precise and accurate numerical method to compute the seismic demands of high-rise structures but is complex, rigorous, and time-consuming and requires a lot of expertise for nonlinear modelling and results interpretation. Therefore, practicing engineers in developing countries like Pakistan still use the simplified analysis procedures to compute the seismic demands. Among the simplified analysis procedures, equivalent lateral force and response spectrum analysis procedures are widely used for the design purpose. However, other procedures have also been proposed in the recent past to accurately capture the higher mode effects in mid-to-high-rise structures. In the current study, results of a forty-story core wall building are used to check the relative accuracy and ease of application of different simplified analysis procedures. Furthermore, a modal decomposition technique is used to separate the modal responses from the NLRHA results, and a mode wise comparison of different demand parameters for different simplified procedures is performed. The current study has been used to clearly identify the reasons of inaccuracies in different simplified procedures. Furthermore, a simplified analysis procedure is proposed to accurately estimate the seismic demands of high-rise buildings and the possible solutions to improve their predictions.